1952
DOI: 10.1136/bmj.2.4781.409
|View full text |Cite
|
Sign up to set email alerts
|

End-results in Primary Sterility

Abstract: EVENTS OF THE PRIMATE OVARIAN CYCLE BR 4 cians of the opportunities they will have to help solve the problems of ovarian function. The basic outline of the human cycle has been worked out, and it can be understood in relation to the general pattern of mammalian reproduction. Its time-schedule is fairly well known statistically. Much has been learned about the endocrine factors that control cyclic events. Because we have gone so far it is becoming possible to study some of the major variations and abnormalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

1953
1953
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…On the other hand, Bender (1952) and Jeffcoate (1954) both reported a conception rate of 46.3%, and Wilson et al (1959) one of 499% from the Mayo Clinic. But there have been comparatively low rates, such as 23 % in 707 cases reported by Barns et al (1953).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, Bender (1952) and Jeffcoate (1954) both reported a conception rate of 46.3%, and Wilson et al (1959) one of 499% from the Mayo Clinic. But there have been comparatively low rates, such as 23 % in 707 cases reported by Barns et al (1953).…”
mentioning
confidence: 97%
“…The outcome of the first pregnancy is summarized iin (Bender, 1952;Southam and Buxton, 1957;Swyer, 1959).…”
mentioning
confidence: 99%
“…Reports that differentiate between treatment related and treatment independent preganacies are not common in recent literature on infertility. Fifty years back Bender [9] found that 63% of 324 pregnancies among 700 couples occurred six months or more after treatment and Sharman [10] reported that 236 of 264 pregnancies among 1575 couples occurred in untreated couples. In 1969 Grant [11] reported that 35% of 1415 women conceived without treatment Dunphy [12] reported 22% pregnancy rate as placebo response in sub-fertile couples.…”
Section: Resultsmentioning
confidence: 99%
“…There is no agreement on length of time after completion of treatment during which its effect may be expected to persist Interval of six months [9,15] and three months [14] after the medical treatment and 12 months after surgical treatment have been reported. We classified pregnancies occurring 3 months after medical treatment and 12 months after the surgical treatment as treatment independent pregnancies as per criteria used by Collins [15] …”
Section: Resultsmentioning
confidence: 99%
“…By two years 249 (95.4%) had conceived. Bender (1952) found that of 714 primigravidae seen 77.4% had conceived within one year of first coitus or marriage, and 86.7% within two years. Tietze et al (1950), reviewing the time required for conception in 1,727 pregnaracies, found that more than 90%Yi had conceived within one year.…”
mentioning
confidence: 99%